INFLUENCE OF pH ON THE CREATION AND GROWTH OF WATER-SOLUBLE CdTe QUANTUM DOTS - Diệu Thuý, Ứng Thị; Toàn, Phạm Song; Liêm, Nguyễn Quang (Vietnam Journal of Science and Technology, 2012)
SUMMARY In this paper we present the study of the influence of pH on the creation and growth of CdTe quantum dots in aqueous phase. The high quality of water-soluble CdTe quantum dots are confirmed through their X-ray diffraction pattern and transmission electron microscope (TEM) image. pH of the reaction medium affects significantly to the optical properties of the synthesized CdTe quantum dots, namely the photoluminescent spectra possess full width at half maximum of 32 – 85 nm corresponding to the pH range of 7 – 12, respectively. At pH = 7 – 8, the CdTe quantum dots are best in quality with quasi-spherical shape, mean size of 2.5 – 5.0 nm depending on the growth time, size dispersion of 10%, and luminescence quantum yield of 40 – 60%.